2017
DOI: 10.1111/epi.13634
|View full text |Cite
|
Sign up to set email alerts
|

Progress report on new antiepileptic drugs: A summary of the Thirteenth Eilat Conference on New Antiepileptic Drugs and Devices (EILAT XIII)

Abstract: SUMMARYThe Thirteenth Eilat Conference on New Antiepileptic Drugs and Devices (EILAT XIII) took place in Madrid, Spain, on June 26-29, 2016, and was attended by >200 delegates from 31 countries. The present Progress Report provides an update on experimental and clinical results for drugs presented at the Conference. Compounds for which summary data are presented include an AED approved in 2016 (brivaracetam), 12 drugs in phase I-III clinical development (adenosine, allopregnanolone, bumetanide, cannabidiol, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
125
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(132 citation statements)
references
References 167 publications
(448 reference statements)
6
125
0
1
Order By: Relevance
“…Unlike benzodiazepines, the site of allopregnanolone binding to the GABAaR for PAM activity is on the α subunit. Unlike benzodiazepines, which bind at the interface between α and β subunits, the binding site for allopregnanolone allows for modulation of both synaptic GABA A Rs and extrasynaptic GABA A Rs, the latter not being internalized during SE 15, 16…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike benzodiazepines, the site of allopregnanolone binding to the GABAaR for PAM activity is on the α subunit. Unlike benzodiazepines, which bind at the interface between α and β subunits, the binding site for allopregnanolone allows for modulation of both synaptic GABA A Rs and extrasynaptic GABA A Rs, the latter not being internalized during SE 15, 16…”
Section: Discussionmentioning
confidence: 99%
“…Allopregnanolone is a potent, endogenously produced neuroactive steroid that acts as a positive allosteric modulator (PAM) on a broad range of γ‐aminobutyric acid type A receptor (GABA A R) isoforms12, 13, 14, 15, 16 expressed throughout the brain, including those that mediate either phasic or tonic inhibition 17, 18, 19. Extrasynaptic receptors containing the δ‐subunit that mediate tonic inhibition are particularly sensitive to modulation by neurosteroids 18.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using our procedure, we have clearly demonstrated that fenfluramine significantly decreased epileptiform activity in the scn1 mutant zebrafish (Sourbron et al , 2016). As fenfluramine has shown effectiveness in patients with Dravet syndrome in an ongoing 27-year observational study in Belgium (Ceulemans et al , 2012; and reviewed in Bialer et al , 2017), we assert that our approach is scientifically sound, and represents a validated testing platform for the discovery of therapeutics in the field of Dravet research. Significantly, using the same model it was shown that fenfluramine is also active after short incubations at 10-fold higher concentrations (Dinday and Baraban, 2015).…”
mentioning
confidence: 89%
“…In that paper we further concluded that the findings open up new possibilities in the search for effective drugs to treat patients with Dravet syndrome. For this reason, but also because clinically tested fenfluramine is known to exert its action through a serotonergic mechanism (Bialer et al , 2017), we believe that the conclusion drawn by Griffin et al (2017) that 5-HT signalling represents a ‘novel’ therapeutic intervention for the treatment of patients with Dravet syndrome is invalid.…”
mentioning
confidence: 99%